Vývoj projevů osobnostních rysů: studie na hraboši polním (Microtus arvalis) - Urbánková, Gabriela (Jihočeská univerzita, 2013)
The aim of this study was investigate the development of behaviour of common vole in usually used personality test - Open Field test. This study also used a new behavioural approach ? behavioural reaction norms - to investigate the relationship among personality traits, behavioural plasticity and body weight and chosen social characteristic. There were found the effects of adult body weight and litter size on individual behavioural plasticity and also the negative correlation between personality traits and behavioural plasticity, signaling the different level of habituation dependent on personality traits.
The development of an expression of personality traits: the common vole (Microtus arvalis) study
Keywords: hraboš polní; vývoj chování; osobnostní typy; behaviorální reakční normy; habituace; common vole; development of behaviour; personality traits; behavioural reaction norms; habituation